Dural Arteriovenous Fistulae: Noninvasive Diagnosis with Dynamic MR Digital Subtraction Angiography - Coley, Stuart C.; Romanowski, Charles A. J.; Hodgson, Timothy J.; Griffiths, Paul D. (American Journal of Neuroradiology, 2002)
Summary: MR digital subtraction angiography (DSA) is a new diagnostic tool capable of producing dynamic images of the cerebral circulation with the injection of gadopentetate dimeglumine into a peripheral vein. Previous reports have concentrated on its potential as a noninvasive technique for the study of pial arteriovenous malformations. In this report, we present our early findings with MR DSA in the evaluation of intracranial dural arteriovenous fistulae.